Bending strength properties of finger joint from Nyatoh (Palaquium spp) - Abd Razak, Muhammad Hairul; Baharin, Muhammad Nor Izham; Zolkapli, Mohd Shah Fitri (2010)
Finger jointing is one of the popular jointing in wood products based in wood industry. At the present this product is the most popular in the furniture industry as substitute material to replaces the solid wood in building construction and furniture manufacturing. This study was related with the objectives to determine the bending strength properties of two type of size and two type of adhesive using Nyatoh (Palaquium spp). The two type of size of finger include 3 cm x 3 cm and 3 cm x 5 cm where its size are bonding or connect with twp type of adhesive, Polyvinyl acetate, PYa A (fast drying) and Polyvinyl acetate, PYa B(slow drying) resin. The implementation of bending testing generally to find the strength properties of the specimen. After finish the study we, get that the 3 cm x 5 cm sizes of timber produce high in strength then 3 cm x 3 cm. It happen because 3 cm x 5 cm sizes of timber have more surface area are bonded or contact with resin. For adhesive we conclude that PYa A are stronger than PYa B. PYa A produce high strength and durable because chemical base solution and have high density when curing. Therefore, the strength properties of size and adhesive are compare with solid wood standard of Nyatoh (Palaquium spp). It is hope that the value derived from this study can be a beneficial guide in assessing the properties of two type of size and two type of adhesive specimen.